Rock climbing-related subclavian vein thrombosis - Lutter, Christoph; Monasterio, Erik; Schöffl, Volker (BMJ Case Reports, 2015)
Paget-Schroetter syndrome, also known as upper extremity deep venous thrombosis (UEDVT), is a rare condition, characterised by a (sub-) total occlusion of the axillary-subclavian venous system due to thrombosis. UEDVT is the most common vascular condition among athletes so far; although the general incidence is low, this problem will become more frequent as a result of increased participation in climbing sports. The purpose of this report is to illustrate two cases in rock climbers where UEDVT developed during rock climbing or bouldering. Fortunately, both patients were diagnosed relatively early after the symptoms began, despite the ambiguity of UEDVT symptoms. This relatively unfamiliar condition may become more highly recognised as a potentially serious differential diagnosis of unspecific pain of the shoulder. Rock climbers are disposed to develop UEDVT due to frequent stress on the upper extremities during training or competition.
EVALuna2:15845